Yoga for the rest of us [videorecording (DVD)] : a step-by-step yoga workout - Baynard, John; Markowitz, Alice; Cappy, Peggy (WGBH Boston Video, 2004)
Will ease you into the world of yoga-whatever your age or ability-and can become your personal at-home trainer. Discover how easily yoga can be incorporated into your daily routine and how quickly you'll see the benefits for your body and spirit.